Enhancing compassion in end-of-life care through drama the silent treatment - Jeffrey, Ewan; Jeffrey, David (Radcliffe, 2013)
This book will motivate all members of the multidisciplinary palliative care team including palliative care professionals, doctors, nurses, psychologists, spiritual advisers and social workers. Although based in the setting of palliative care, the learning points are relevant to all areas of clinical practice